Innovative Therapy for Diabetes Mellitus Based on Tithonia Diversifolia Through Pancreatic β-Cell Viability: english - Fitriyanto, Raden Edi (Asian Journal of Innovation and Entrepreneurship, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease with increasing global prevalence including in Indonesia. A key factor in the pathogenesis of DM is damage to pancreatic β cells which are essential for insulin production. This study aims to determine the effect of ethanol extract of Tithonia diversifolia leaves on blood glucose levels and pancreatic β cells in DM model rats. Tithonia diversifolia contains flavonoids and polyphenols which possess antioxidant properties. These compounds may reduce the production of reactive oxygen species (ROS) and offer cell protection The study used a laboratory-based experimental post-test only control group design. Four groups were used: a negative control group (K); three treatment groups (P1, P2, and P3) receiving T. diversifolia ethanol extract at doses of 50, 150, and 500 mg/kg body weight/day. Each group consisted of 9 males diabetic Wistar rats induced by streptozotocin. The results showed that the administration of T. diversifolia ethanol extract at a dose of 150 mg/kgBW/day resulted in a significantly higher average pancreatic β-cell count compared to the control group and the 50 and 500 mg/kg body weight (BW)/day treatment groups.